Numerical evaluation of mechanical behaviour of lattice structures for rotating blades - Pir, İnci; Şahin, Serhat Arda; Tüfekci, Mertol; Tüfekci, Ekrem (Institute for Materials, Technologies and Mechanics, 2024)
Lattice structures have significant potential in engineering, allowing for material and weight reduction while maintaining desired mechanical properties. This versatility is crucial in applications ranging from aerospace to medical implants, where customisability and efficiency are essential. This study investigates the mechanical performance of four lattice structures with multiple and single-cell model approaches. The aim is to elucidate the impact of lattice design parameters on the structural integrity and performance of components subjected to dynamic loads typical of rotating blades in aerospace applications. Utilising Finite Element Analysis (FEA), this research is conducted to characterise the overall mechanical behaviour and to simulate the behaviour of these structures under conditions that represent real-world operational conditions for rotating blades. The loading conditions considered are tension, compression, shear and periodic boundary conditions are applied. By comparing the mechanical behaviour of these lattice structures against each other, this research aims to identify optimised lattice designs that enhance the performance and durability of rotating blades. This study is expected to contribute to the broader field of materials science and engineering by providing guidelines for designing more efficient, lightweight, high-performance components in various industrial applications.
Keywords: lattice structures; finite element analysis; mechanical behaviour; periodic boundary conditions; specific stiffness